Mutational Spectrum, Copy Number Changes, and Outcome: Results of a Sequencing Study of Patients With Newly Diagnosed Myeloma - Walker, Brian A; Boyle, Eileen M; Wardell, Christopher P; Murison, Alex; Begum, Dil B; Dahir, Nasrin M; Proszek, Paula Z; Johnson, David C; Kaiser, Martin F; Melchor, Lorenzo; Aronson, Lauren I; Scales, Matthew; et al. (Journal of clinical oncology, 2015)
PURPOSE: At the molecular level, myeloma is characterized by copy number abnormalities and recurrent translocations into the immunoglobulin heavy chain locus. Novel methods, such as massively parallel sequencing, have begun to describe the pattern of tumor-acquired mutations, but their clinical relevance has yet to be established. METHODS: We performed whole-exome sequencing for 463 patients who presented with myeloma and were enrolled onto the National Cancer Research Institute Myeloma XI trial, for whom complete molecular cytogenetic and clinical outcome data were available. RESULTS: We identified 15 significantly mutated genes: IRF4, KRAS, NRAS, MAX, HIST1H1E, RB1, EGR1, TP53, TRAF3, FAM46C, DIS3, BRAF, LTB, CYLD, and FGFR3. The mutational spectrum is dominated by mutations in the RAS (43%) and nuclear factor-κB (17%) pathways, but although they are prognostically neutral, they could be targeted therapeutically. Mutations in CCND1 and DNA repair pathway alterations (TP53, ATM, ATR, and ZNFHX4 mutations) are associated with a negative impact on survival. In contrast, those in IRF4 and EGR1 are associated with a favorable overall survival. We combined these novel mutation risk factors with the recurrent molecular adverse features and international staging system to generate an international staging system mutation score that can identify a high-risk population of patients who experience relapse and die prematurely. CONCLUSION: We have refined our understanding of genetic events in myeloma and identified clinically relevant mutations that may be used to better stratify patients at presentation.
Keywords: vysoce účinné nukleotidové sekvenování; Male; lidé středního věku; Prospective Studies; Humans; Survival Analysis; mnohočetný myelom; Middle Aged; ras Proteins; prospektivní studie; mužské pohlaví; Multiple Myeloma; Female; United Kingdom; Ras proteiny; DNA Mutational Analysis; Proportional Hazards Models; ženské pohlaví; mutační analýza DNA; variabilita počtu kopií segmentů DNA; Genetic Predisposition to Disease; mladý dospělý; Adult; Young Adult; proporcionální rizikové modely; analýza přežití; multivariační analýza; Spojené království; genetická predispozice k nemoci; dospělí; lidé; DNA Copy Number Variations; Multivariate Analysis; High-Throughput Nucleotide Sequencing